FEATURES OF THE DEVELOPMENT OF PUBLIC-PRIVATE PARTNERSHIP IN THE FIELD OF VOCATIONAL EDUCATION AND TRAINING IN THE REPUBLIC OF POLAND (Innovative professional education, 2024)
The state and prospects and features of the development of public-private partnership in the field of professional education in Poland are analyzed, the regulation of such partnership at the level of Polish national legislation is studied. The general prospects of applying the experience of European countries in Ukraine were assessed.
Keywords: public-private partnership, Poland, European experience, legislation